The Effect of Feed on Herd Replacement Indicators in Cows - S.M. Buriqulov; M.K. Narbayeva (American Journal of Botany and Bioengineering, 2026)
The inclusion of additional feed in the diet of dairy cows has a positive effect on herd replacement indicators. It ensures optimal duration of the service period and calving interval, enables obtaining one calf per cow annually, and increases the herd replacement coefficient by approximately 1.0–2.0%.